Perspectives on Grammaticalization. - Pagliuca, William (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 1994)
This is the second of two volumes deriving from papers presented at the Nineteenth Annual UWM linguistics Symposium held in Milwaukee in 1990. It focuses on the evolution of grammatical form and meaning from lexical material, which has reinvigorated historical analysis and theory and led to advances in the understanding of the relation between diachrony and universals. The richness and potential of some of the leading approaches to grammaticalization are here illustrated in thirteen selected papers.